Young age is associated with favorable characteristics but is not an independent prognostic factor in patients with epithelial ovarian cancer: A single institution experience - Bozas, G.; Dimopoulos, M.A.; Kastritis, E.; Efstathiou, E.; Koutsoukou, V.; Rodolakis, A.; Vlahos, G.; Voulgaris, Z.; Papageorgiou, T.; Gika, D.; Papadimitriou, C.; Bamias, A. (Oncology, 2006)
Background: Young age has been reported to be a favorable prognostic factor in ovarian cancer. The aim of the present study was to investigate the characteristics of ovarian cancer presenting in patients aged ≤40 and assess the prognostic significance of young age. Methods: Data from 591 consecutive ovarian cancer patients, including 37 subjects (6.3%) aged ≤40, who were treated postoperatively with platinum-based chemotherapy in our institution were retrospectively reviewed. Results: In our series, age ≤40 did not show an independent association with overall (p = 0.542) or progression-free survival (p = 0.334). Nonetheless, it was correlated with low tumor grade (p = 0.009) and small volume of residual disease after primary surgery (p = 0.020), while there was a nonsignificant trend for correlation with performance status 0 (p = 0.052). Stratified analysis showed that age ≤40 was associated with improved overall survival in the subgroups of serous histology and stage IIC-IV disease; however, multivariate analyses failed to identify age as an independent predictor of survival within either subgroup (p = 0.079 and p = 0.585, respectively). Conclusions: Age ≤40 was not an independent prognostic factor in our analysis.The survival advantage of young patients may be attributed to the association with low tumor grade, more complete surgical debulking and better performance status. Copyright © 2006 S. Karger AG.
Keywords: Epithelial ovarian cancer; Young age as prognostic factor